Clinical Implications of the Association Between Temporal Bone Tegmen Defects and Superior Semicircular Canal Dehiscence. Issue 6 (July 2018) - Handzel, Ophir; Brenner-Ullman, Adi; Cavel, Oren; Oron, Yahav; Wasserzug, Oshri; Fliss, Dan M.; Ungar, Omer J.
Abstract : Objective: To discuss the clinical implications of the association between temporal bone tegmen dehiscence (TD) necessitating surgical correction and the adjacent dehiscent superior semicircular canal (SSCD). Study Design: Retrospective. Setting: Tertiary referral center. Patients: Sixteen patients with idiopathic TD, with or without SSCD, requiring surgical correction. Interventions: Corrective surgery for TD. High-resolution temporal bone-targeted computed tomography. Main Outcome Measures: The impact of the minimal distance between TD and SSCD or the arcuate eminence on the choice of surgical approach to TD. Results: The patients' median age was 58 years and 5 were males. The median body mass index was 31.8 kg/m 2 . The average distance from the TD and the SSC was 4.9 mm (range 2.1–14.2 mm). Three of the 14 patients who were operated via a temporal craniotomy to fix a cerebrospinal fluid-leaking TD required plugging of an asymptomatic SSCD due to its close proximity (3–5 mm) to the defect, and two of them had relatively protracted vestibular recuperation. Two patients were operated via a transmastoid approach for sealing a cerebrospinal fluid-leaking TD coexisting with a bilateral asymptomatic SSCD. No patient had a hearing loss. Conclusion: The close proximity of a TD and an SSCD might not allow selective exposure. As a result, asymptomatic SSCD may become symptomatic during TD correction via the temporal craniotomy approach. The need to plug an asymptomatic SSCD that is proximal to a TD should be factored in planning for surgery and rehabilitation. The choice of surgical approach (middle fossa vs. transmastoid) could be influenced by this relationship, especially in cases of bilateral lesions.